2019
DOI: 10.1002/brb3.1218
|View full text |Cite
|
Sign up to set email alerts
|

Random topology organization and decreased visual processing of internet addiction: Evidence from a minimum spanning tree analysis

Abstract: Objectives Internet addiction (IA) has been associated with widespread brain alterations. Functional connectivity (FC) and network analysis results related to IA are inconsistent between studies, and how network hubs change is not known. The aim of this study was to evaluate functional and topological networks using an unbiased minimum spanning tree (MST) analysis on electroencephalography (EEG) data in IA and healthy control (HC) college students. Methods In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
2
2
1
1
Order By: Relevance
“…First, we performed correlation analyses to confirm the association between the alpha-bands K and D, beta-bands K and D, and smartphone use disorder. Consistent with a previous study ( H. Wang, Sun et al., 2019 ), smartphone use disorder was positively associated with alpha band K and negatively associated with alpha band D (see Table 3 ). However, we did not find a significant correlation between beta-bands K and D and smartphone use disorder.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…First, we performed correlation analyses to confirm the association between the alpha-bands K and D, beta-bands K and D, and smartphone use disorder. Consistent with a previous study ( H. Wang, Sun et al., 2019 ), smartphone use disorder was positively associated with alpha band K and negatively associated with alpha band D (see Table 3 ). However, we did not find a significant correlation between beta-bands K and D and smartphone use disorder.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, this change increased the traffic loads at the hubs and the risk of hub overload, which, in turn, compromised the global network ( Stam, 2014 ). Previous research reported that internet use disorder and problematic social networking site use also showed a star-like topology of the rs-EEG brain network in the alpha band, like our results ( H. Wang, Sun et al., 2019 ; Yin et al., 2023 ). Thus, for the first time, our findings reveal a close relationship between topological deviations of rs-EEG brain networks and smartphone use disorder.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Namun, hal tersebut menimbulkan berbagai masalah bagi individu yang tidak bisa mengontrol penggunaan waktu, sehingga risiko penggunaan berlebih mungkin terjadi. Hal tersebut menyebabkan efek buruk perkembangan psikososial untuk remaja (Tahiroglu, Celik, Uzel, Ozcan, & Avci, 2008;Wang, Sun, Lv, & Bo, 2019). Kondisi ini disebabkan karena lemahnya kontrol diri (Davis, 2001b;Özdemir, Kuzucu, & Ak, 2014;Young & Rogers, 1998;Li, Hou, Yang, Jian, & Wang, 2019) mahasiswa untuk mengatur waktu dalam penggunaan internet setiap hari.…”
Section: 233unclassified